Perceptions and opinions regarding human papilloma virus vaccination among young women in Malaysia - Al-Naggar, Redhwan Ahmed; Al-Jashamy, Karim; Chen, Robert (West Asia Organization for Cancer Prevention, 2010)
Objective: The objective of this study is to explore the perceptions and opinions of young women about human papilloma virus (HPV) vaccination and associated barriers. Methodology: This qualitative in-depth interview study was conducted in January 2010 with 30 university students from different faculties, i.e.:International Medical School (IMS), Faculty of Health and Life Sciences (FHLS), Faculty of Business Management and Professional Studies (FBMP) and Faculty of Information Sciences and Engineering (FISE) of the Management and Science University (MSU), Shah Alam, Malaysia. After consent was obtained from all participants, the interviewer wrote down the conversations during the interview sessions. The data obtained were classified into various categories and analyzed manually. Results: The majority of participants 25 (83%) had heard about cervical cancer, while 16 (53.3%) have never heard of HPV. Only five participants (17%) mentioned that HPV is the cause of cervical cancer. Ten participants (33.3%) did not know any causes. The majority 16 (53.3%) did not know the mode of HPV transmission. The majority of participants 22 (73.3%) mentioned that they had not been vaccinated against HPV. Out of 22, 16 (53.3%) agreed to be vaccinated in the future to protect themselves from cervical cancer and five (17%) participants mentioned they are not willing because of the uncertain safety of the available vaccines and their side effects. Conclusion: This study showed relatively poor knowledge about HPV and its vaccines, pointing to urgency of educational campaigns aimed at students in the public and government universities to promote HPV vaccination among this highly eligible population.